CAN-drivers & graphical user interface in LabVIEW - Karlsson, Kenneth; Liljekrantz, Johan (My University, 2008)
Lab VIEW® is a widely used programming tool for creating graphical user interfaces. CAN is the most common protocol for communication in cars. In this thesis the combination of the two is studied. This thesis documents the testing of the USB-8473s hardware for CAN-communication using Lab VIEW® as a programming tool. Drivers for the hardware were developed and standardized. Also a graphical user interface with capabilities of diagnostics using the D2-protocol, graphical monitoring of CAN-channels over time, logging CAN-traffic, basic CAN-communication as well as a demo-mode for demonstrating the connection between a computer and the car have been developed. The graphical user interface was designed with a flexible structure that was event based, making it easy to implement additional features. The report also covers the structure of the program and some programming details.